0669 The Effects Of Continuous Positive Airway Pressure Therapy In Moderate To Severe Obstructive Sleep Apnea: A High-density EEG Study. (27th May 2020) - D'Rozario, A L; Kao, C; Mullins, A E; Memarian, N; Yee, B; Duffy, S; Banerjee, D; Cho, G; Wong, K K; Kremerskothen, K; Chapman, J; Haroutonian, C; et al.
Abstract: Introduction: A previous high-density electroencephalography (EEG) investigation in asymptomatic OSA showed regional deficits in sleep EEG power particularly slow wave activity (SWA) during NREM sleep in the parietal region. It is unclear whether treatment with CPAP can reverse local sleep EEG abnormalities in OSA, and whether any recovery is related to improvement in sleep-dependent memory consolidation. Methods: Fifteen male participants (age 50.4±6.5yrs, AHI 51.7±23.5/h) with moderate-severe OSA (AHI>15/h) underwent overnight polysomnography with 256-channel high-density EEG at baseline and following 3 months of CPAP therapy. A word paired associates declarative memory task was administered before and after sleep. After artefact removal, spectral analysis was performed for all channels. Topographical power maps were calculated for standard frequency ranges for NREM sleep (164 channels within a 0.57 radius from the vertex). Maps were compared using both absolute and normalized power (z-scores computed for each subject) and differences between baseline and treatment were determined by statistical nonparametric mapping. Results: In 11 CPAP compliant patients (intolerant of CPAP [n=3]/high-density EEG [n=1]), analysis of polysomnographic variables showed that total sleep time did not differ but N1 (baseline vs. treatment: 66.9 vs. 39.5 mins, p=0.008) and N2 (195.0 vs. 150.6 mins, p=0.002) sleep was lower and N3 (89.8 vs. 128.7 mins, p=0.003) was higher after CPAP. Topographic analysis of high-density EEG data revealed a regional increase in SWA (1-4.5Hz) EEG power during N3 sleep in a cluster of electrodes overlying the centro-parietal cortex (cluster mean t-value=2.87, p=0.02). The change in overnight declarative memory consolidation (% recognition) after CPAP was significantly correlated with the change in slow spindle frequency activity in frontal regions (cluster mean r=0.875, p=0.003). Conclusion: CPAP treatment may enhance localised deficits in sleep EEG activity in OSA, and specific regional recovery may translate to memory improvements in the short-term. These data also highlight the potential for long-term therapeutic effects on cognitive outcomes in OSA. Support: